Front Matter - Muchaluat-Saade, Débora C.; Abreu, Jorge Ferraz de; Moraes, Igor Monteiro; Ghinea, George; Conci, Aura; Broeck, Wendy Van den (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences Workshops, 2025)
Este documento apresenta o front matter dos anais do ACM IMXw 2025.